Methods and validation of velacur determined fat fraction in patients with MASLD - Mohammad Honarvar; Julio Lobo; Caitlin Schneider; Samuel Klein; Gordon I. Smith; Rohit Loomba; Alnoor Ramji; Tarek Hassanein; Eric M. Yoshida; Emily Pang; Michael P. Curry; Nezam H. Afdhal (WFUMB Ultrasound Open)
Introduction: As prevalence of patients with steatotic liver diseases increases throughout the world, it is necessary to have accurate and accessible methods to estimate liver fat content. Using quantitative ultrasound parameters, such as attenuation and backscatter, it is possible to estimate liver fat with MRI proton density fat fraction as the reference standard. Velacur determined fat fraction (VDFF) is a new output measurement on Velacur (Sonic Incytes Medical Corp, Vancouver, BC). Methods: This study described the results of parameter fitting and validation of VDFF, which is a combination of quantitative ultrasound parameters. Patients were recruited from sites within the US and Canada. All patients had contemporaneous Velacur and MRI proton density fat fraction scans. The quantitative ultrasound parameter fitting was completed using linear regression on a random sub-sample approach, and a separate cohort was used for validation. The AUC for detection of 5 % liver fat based on MRI-PDFF and the correlation between MRI-PDFF and VDFF was measured in both cohorts. Results: VDFF had an AUROC of 0.97 for the detection of MRI-PDFF >5 % in the parameter fitting cohort, and 0.99 in the validation cohort. The correlation [95 % CI] between MRI-PDFF and VDFF was r = 0.84 [0.78–0.89] for the parameter fitting cohort and r = 0.90 [0.82–0.95] for the validation cohort. Conclusion: The Velacur Determined Fat Fraction (VDFF) is an accurate and accessible way to estimate steatosis as measured by MRI-PDFF. Velacur VDFF can fill the unmet need of an accurate means to diagnosis hepatic steatosis and serve as a potential alternative to biopsy or MRI-PDFF.